Konstruksi Pesan Kemanusiaan dan Pemulihan Psikososial Pascabencana di Aceh, Sumatera Utara, dan Sumatera Barat dalam Konten Instagram @aniesbaswedan - Dhea Syafitri; Habibullah Ya Ramadhan; Fatwa Azan Aldifa; Rahmanita Ginting (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
This study aims to analyze the construction of the meaning of humanitarian messages and psychosocial recovery as well as the representation of the role of actors, empathy, and social solidarity in Instagram content @aniesbaswedan in the post-disaster situation in Aceh, North Sumatra, and West Sumatra. The study used a qualitative method with a content analysis design, referring to the Krippendorff approach, on 22 Instagram posts for the period of November 27–December 23, 2025 which were analyzed interpretively through thematic categorization and interpretation of latent meaning. The results showed that humanitarian messages were constructed through empathic narratives, the use of inclusive diction, visual direct engagement with survivors, as well as an emphasis on collective solidarity and the sustainability of recovery, while psychosocial recovery was represented as a long-term social process involving non-survivor actors, community social capital, dignity values, and recognition of the emotional and cultural experiences of affected communities. These findings confirm that content @aniesbaswedan serves as an alternative digital public space that complements the state's formal narrative in responding to disasters. This study recommends strengthening empathic, participatory, and community-based post-disaster communication strategies for governments, humanitarian organizations, and public figures, as well as encouraging cross-platform follow-up research and audience approaches to deepen the study of humanitarian communication and psychosocial recovery.